Actuating Mood: Design of the Textile Mirror - Davis, Felecia; Roseway, Asta; Carroll, Erin; Czerwinski, Mary (TEI 2013, 2013)
In his 1962 short story, “1000 Dreams of Bellavista,” sci-fi author J.G Ballard describes a future in which “psychotropic” homes exist and are designed to “feel and react” to the emotions of their occupants [1]. Today with the rise of affective computing, and advancements in etextiles, smart materials and sensor technologies, we must consider the ramifications of technology that could actively mirror, alter and transform our feelings through the materials that make up our buildings and environments. This work provides discussion and insight around the binding of material and sensor technologies with affect. We investigate how emotions could be mapped to our environment through textiles. We present two online surveys designed to enable people to map emotions to textiles. We then use the results of these surveys to inform and inspire the design of the Textile Mirror prototype, a 60x92 cm wall panel that is composed of industrial felt interlaced with Nitinol wire, and is designed to shift its textural structure upon receiving emotional signals from its viewer.